2017
DOI: 10.1097/mib.0000000000000975
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Intestinal Microbiota Following Combination Therapy with Fecal Microbial Transplantation and Antibiotics for Ulcerative Colitis

Abstract: FMT following antimicrobial bowel cleansing synergistically contributes to the recovery of the Bacteroidetes composition, which is associated with clinical response and UC severity. Thus, this therapeutic protocol may be useful for managing UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
115
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(122 citation statements)
references
References 38 publications
4
115
0
3
Order By: Relevance
“…Previous studies demonstrated that the microbiota in the small intestine is less stable than that in the large intestine (Gu et al, 2013; Kelly et al, 2017; Li et al, 2017), which suggests that the microbiota in the small intestine may be susceptible to environmental factors. In support of this idea, FMT has been demonstrated to be most effective in diseases of the large intestine diseases, such as CDI or IBD (Fuentes et al, 2014; Bagdasarian et al, 2015; Marchesi et al, 2016; Ishikawa et al, 2017). The FMT efficiency on diseases of the small intestine still needs further research.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Previous studies demonstrated that the microbiota in the small intestine is less stable than that in the large intestine (Gu et al, 2013; Kelly et al, 2017; Li et al, 2017), which suggests that the microbiota in the small intestine may be susceptible to environmental factors. In support of this idea, FMT has been demonstrated to be most effective in diseases of the large intestine diseases, such as CDI or IBD (Fuentes et al, 2014; Bagdasarian et al, 2015; Marchesi et al, 2016; Ishikawa et al, 2017). The FMT efficiency on diseases of the small intestine still needs further research.…”
Section: Discussionmentioning
confidence: 91%
“…Intestinal microbial disorders have been demonstrated to be related to multiple human diseases such as Clostridium difficile infection (CDI; Fuentes et al, 2014; Bagdasarian et al, 2015), inflammatory bowel disease (IBD; Marchesi et al, 2016; Ishikawa et al, 2017), obesity (Ridaura et al, 2013; Boulangé et al, 2016), and mental illness (Foster and McVey Neufeld, 2013; Zheng et al, 2016). Consequently, reprogramming gut microbiota is a promising approach to redressing intestinal and physiological disorders (Cammarota et al, 2014; Petrof and Khoruts, 2014; Zheng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fecal microbiota transfer (FMT) has proven to be a effective way to transfer “healthy” microbiota, that may have beneficial effects on metabolism and the immune system in recipient mice (30, 95). FMT has also been used in patients with colitis (9698) and recently in cancer patients (99, 100). We recently demonstrated that FMT could restore the gut microbiota and rebalance the gut hemeostasis, which in turns delayed diabetes onset in NOD mice (26, 29).…”
Section: Fecal Microbiota Transfer (Fmt) As a Potential Therapymentioning
confidence: 99%
“…FMT from lean mice to obese mice can ameliorate the metabolic syndrome in the obese mice due to the rebalancing of gut microbiota (101). Treating metabolic syndrome with FMT has also been tested in humans [98]. …”
Section: Fecal Microbiota Transfer (Fmt) As a Potential Therapymentioning
confidence: 99%